An ultra-small active nanofluid and its preparation method and application

By using ultra-small size active nanosilicon dots with particle sizes of 3 to 5 nm as oil repellent in low permeability reservoirs, the problem of poor effectiveness of conventional chemical flooding in high temperature and high salt environments is solved, and the oil film peeling efficiency and procurement are achieved Significant improvement in yield.

CN115991982BActive Publication Date: 2024-12-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202111216812.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-19
Publication Date
2024-12-13
Estimated Expiration
2041-10-19

AI Technical Summary

Technical Problem

Due to low porosity and small pore throat, conventional chemical drives are difficult to apply, polymers are prone to blockage, and their effectiveness is difficult to exert in high-temperature and high-salt environments, resulting in low recovery.

Method used

Ultra-small size active nanosilicon dots with particle size of 3 to 5 nm, with high interfacial activity and temperature and salt resistance. By reducing oil-water interface tension and enhancing the interface viscoelastic modulus, it is used as an oil-repellent repellent in low permeability reservoirs. , improve recovery rate.

Benefits of technology

The recovery rate of low-permeability reservoirs has been significantly improved, the oil film peeling efficiency has been increased by more than 40%, the production degree has been increased by more than 15%, and it is environmentally friendly and easy to formulate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115991982B_ABST
    Figure CN115991982B_ABST
Patent Text Reader

Abstract

The present invention discloses an ultra-small-sized active nanofluid, which is composed of 0.05-0.2wt% of ultra-small-sized active nano-silicon dots and water. A method for preparing an ultra-small-sized active nanofluid comprises (1) preparing an ultra-small-sized active nano-silicon dot solid powder; (2) dissolving the ultra-small-sized active nano-silicon dot solid powder in water to prepare a mother liquor; (3) adding water to the mother liquor under stirring conditions to dilute it to a concentration of 0.05-0.2wt%. The ultra-small-sized active nanofluid is used as an oil displacement agent for low permeability reservoirs. The present invention has the following beneficial effects: (1) high compatibility with nano-micro pore throats of low permeability reservoirs, easy to enter nano-micro pore throats, and little damage to pore throats; (2) high interfacial activity, which can significantly reduce the oil-water interfacial tension and improve the recovery rate of low permeability reservoirs; (3) high oil film stripping efficiency; (4) environmentally friendly, self-dispersible, and easy to prepare.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ultra-small size active nanofluid and a preparation method and application thereof, belonging to the technical field of oil and gas field development engineering. Background Art

[0002] Low-permeability reservoirs account for a large proportion of my country's proven oil reserves. The country's cumulative proven geological reserves of oil are about 28.7 billion tons, of which low-permeability reservoirs account for about 14.1 billion tons, accounting for 49%. The remaining oil resources are 79.9 billion tons, of which low-permeability reservoirs account for 43.1 billion tons, accounting for 54% of the total remaining oil resources. At the same time, the proportion of low-permeability reservoirs in crude oil production has been rising year by year.

[0003] The reservoir properties and crude oil properties of low permeability reservoirs are relatively poor. The oil-bearing areas are controlled by a variety of geological factors. The distribution of oil, gas and water, reservoir properties, crude oil properties and fracture development levels vary greatly in different regions. Since the matrix pore throats of low permeability reservoirs are mostly micro-nanoscale (50nm-900nm), the capillary effect is significant, and the oil / water / solid interface effect is prominent in the confined space, the fluid flow resistance is large, and the matrix energy is difficult to replenish, showing "no injection, no production", resulting in low efficiency in the use of matrix pore crude oil. And as the proportion of deep low permeability reservoirs increases year by year, the reservoir conditions have the harsh characteristics of high temperature and high salt, and the efficient development of low permeability reservoirs faces huge challenges.

[0004] my country has abundant low-permeability reservoir resources, but due to its low porosity, small pore throats, and poor seepage capacity, conventional chemical flooding is difficult to apply. For example, the large size of polymer molecules can easily cause serious blockage of pore throats; thermal degradation and chemical degradation at high temperatures cause serious loss of polymer viscosity; surfactants have a large amount of formation adsorption and are sensitive to high-temperature and high-mineralization reservoirs, and are easily hydrolyzed, making it difficult to achieve effectiveness. Therefore, it is urgent to find new high-efficiency materials to solve the above problems, so as to be applicable to the efficient development of low-permeability reservoirs in complex situations such as high temperature and high mineralization.

[0005] Nanomaterials can solve engineering problems that cannot be solved or are difficult to solve in the field of traditional oil extraction due to their special properties, especially their own nano effects. Nanomaterials have small size effects, surface effects, wetting characteristics and shear thickening characteristics, as well as unique thermal, mechanical, magnetic, and chemical properties, and have broad application prospects in the field of improving oil and gas recovery. Its main mechanism is to generate structural separation pressure, change rock wettability, reduce oil-water interfacial tension, inhibit particle migration, etc. Nanoparticles not only have good temperature and salt resistance, but also have a nanometer-scale particle size, which can pass through the nano-scale pore throats of low permeability reservoirs. These unique characteristics of nanoparticles can just solve the problems of conventional chemical flooding, making nanoparticles show great potential in the application of low permeability reservoir recovery technology. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention discloses an ultra-small active nanofluid and its preparation method and application. The present invention exerts the oil displacement effect of the nanofluid and provides a new solution for improving the recovery rate of low permeability oil reservoirs.

[0007] Compared with conventional nano-SiO2 fluids, ultra-small active nano-silicon dots are smaller in size (particle size 3-5nm), more compatible with low-permeability reservoirs, with high interfacial activity, good water dispersibility, and little impact from reservoir environment. They can provide a new method for improving the recovery rate of low-permeability reservoirs.

[0008] Technical solution: An ultra-small active nanofluid composed of the following substances:

[0009] Ultra-small active nano silicon dots, with a content of 0.05-0.2wt%;

[0010] The rest is water.

[0011] Furthermore, the water contains K + 、Na + Mg 2+ , Ca 2+ and Cl - of water, of which K + 、Na + The total concentration is 1000~30000mg / L, Ca 2+ and Mg 2+ The total concentration is 100-2000 mg / L, and the total mineralization is 2000-60000 mg / L.

[0012] Furthermore, the content of the ultra-small active nano silicon dots is 0.1 wt %, and the content of water is 99.9 wt %.

[0013] Furthermore, the particle size of the ultra-small active nano silicon dots is 3 to 5 nm.

[0014] A method for preparing ultra-small active nanofluids comprises the following steps:

[0015] (1) Preparation of ultra-small active nano-silicon dot solid powder;

[0016] (2) dissolving the ultra-small size active nano silicon dot solid powder in water to prepare an ultra-small size active nano silicon dot mother solution for later use;

[0017] (3) Add water to the ultra-small active nano-silicon dot mother solution under stirring conditions to dilute it to a concentration of 0.05-0.2 wt%.

[0018] Furthermore, in parts by mass, step (1) comprises:

[0019] (11) dissolving 0.3-0.5 parts of trisodium citrate in 7-9 parts of ultrapure water, introducing nitrogen gas for protection, and then adding 1.5-2.5 parts of 3-aminopropyltrimethoxysilane, stirring at room temperature to obtain a mixed solution; adding the mixed solution into a high-pressure reactor, heating to 100-240° C., and reacting for 1.5-48 hours to obtain an ultra-small-sized nano-silicon dot solution;

[0020] (12) adding 8 to 12 parts of a 20 to 30 wt% glutaraldehyde aqueous solution and 2 to 4 parts of p-phenylenediamine to 35 to 45 parts of ultrapure water, stirring at room temperature for 5 to 10 hours, adding the ultra-small-sized nano-silicon dot solution obtained in step (11), and continuing to stir at room temperature for 5 to 10 hours to obtain a mixed solution;

[0021] (13) 4 to 6 parts of sodium p-aminobenzenesulfonate and 8 to 12 parts of glutaraldehyde are added to the mixed solution obtained in step (12), and stirring is continued at room temperature for 5 to 10 hours. After freeze-drying, an ultra-small size active nano-silicon dot solid powder is obtained.

[0022] The ultra-small active nanofluid is used as an oil displacement agent for low permeability reservoirs.

[0023] Furthermore, the reservoir temperature of the low permeability oil reservoir is 60-120°C.

[0024] The ultra-small size active nanofluid suitable for oil recovery in low permeability reservoirs provided by the present invention has the following characteristics: a particle size of 3 to 5 nm, a high matching degree between the ultra-small size and the nano-micro pore throats of low permeability reservoirs, a high interfacial activity, the ability to reduce oil-water interfacial tension, and enhance the viscoelastic modulus of the interfacial film; the oil film stripping efficiency can be increased by 40% compared with water, and the recovery degree of low permeability reservoirs can be increased by more than 15%.

[0025] Beneficial effects: The beneficial effects of the present invention are:

[0026] (1) The active nanofluid oil displacement agent suitable for low permeability reservoir oil displacement provided by the present invention has the characteristics of ultra-small size (particle size is 3-5nm), has high compatibility with nano-micro pore throats of low permeability reservoirs, is easy to enter nano-micro pore throats, and has little damage to the pore throats.

[0027] (2) The active nanofluid oil-displacing agent suitable for low permeability oil reservoirs provided by the present invention has high interfacial activity, can significantly reduce the oil-water interfacial tension, and improve the recovery rate of low permeability oil reservoirs.

[0028] (3) The active nanofluid oil-displacing agent suitable for low-permeability oil reservoir displacement provided by the present invention has an oil film stripping efficiency that is more than 60% higher than that of pure water and more than 20% higher than that of surfactants.

[0029] (4) The ultra-small active nanofluid suitable for oil recovery in low permeability reservoirs provided by the present invention is environmentally friendly, self-dispersible, and easy to prepare. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the XPS spectrum of ultra-small active nano-silicon dots.

[0031] Figure 2 This is the infrared spectrum of ultra-small active nano-silicon dots.

[0032] Figure 3 This is a high-resolution transmission electron microscopy (HRTEM) image of ultra-small active nano-silicon dots.

[0033] Figure 4 This is the dynamic light scattering nanoparticle size analysis chart (DLS) of ultra-small active nano-silicon dots.

[0034] Figure 5 It is a schematic diagram of the oil film stripping test results of ultra-small active nanofluids.

[0035] Figure 6 is a graph showing the relationship between the interfacial tension of the ultra-small active nanofluid and the simulated oil and the concentration of the ultra-small active nanofluid.

[0036] Figure 7 is a graph showing the relationship between the viscoelastic modulus of the ultra-small active nanofluid and the simulated oil and the concentration of the ultra-small active nanofluid.

[0037] Figure 8a Schematic diagram of the core displacement process of ultra-small active nanofluids.

[0038] Figure 8b Schematic diagram of the experimental results of core flooding with ultra-small active nanofluids.

[0039] Fig. 9This is a schematic diagram of the low-field nuclear magnetic resonance test results of the ultra-small size active nanofluid oil recovery process. DETAILED DESCRIPTION

[0040] The specific embodiments of the present invention are described in detail below.

[0041] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified.

[0042] Example 1

[0043] An ultra-small active nanofluid, comprising the following substances: ultra-small active nano silicon dots, with a content of 0.1wt%;

[0044] The rest is water.

[0045] The water contains K + 、Na + Mg 2+ , Ca 2+ and Cl - of water, of which K + 、Na + The total concentration is 20000mg / L, Ca 2+ and Mg 2+ The total concentration is 1000 mg / L and the total mineralization is 30000 mg / L.

[0046] Example 2

[0047] An ultra-small active nanofluid, comprising the following substances: ultra-small active nano silicon dots, with a content of 0.05wt%;

[0048] The rest is water.

[0049] The water contains K + 、Na + Mg 2+ , Ca 2+ and Cl - of water, of which K + 、Na + The total concentration is 1000 mg / L, Ca 2+ and Mg 2+ The total concentration is 100 mg / L and the total mineralization is 2000 mg / L.

[0050] Example 3

[0051] An ultra-small size active nanofluid, comprising the following substances: ultra-small size active nano silicon dots, with a content of 0.2wt%;

[0052] The rest is water.

[0053] The water contains K + 、Na + Mg 2+ , Ca 2+ and Cl - of water, of which K + 、Na + The total concentration is 30000mg / L, Ca 2+ and Mg 2+ The total concentration is 2000 mg / L and the total mineralization is 60000 mg / L.

[0054] Example 4: Characterization of ultra-small active nano-silicon dots for oil recovery in low permeability reservoirs

[0055] The ultra-small active nano-silicon dots solid powder was characterized by XPS and infrared spectroscopy, and the elemental composition of the ultra-small active nano-silicon dots and the surface group composition of the ultra-small active nano-silicon dots were analyzed, such as Figure 1 , 2 As shown;

[0056] The 0.1wt% ultra-small active nanofluid prepared in Example 1 was tested by HRTEM and DLS to analyze the microscopic morphology and particle size distribution of the ultra-small active nano silicon dots. Figure 3 , 4 The particle size of HRTEM is 2-4 nm, and it has a spherical structure, and the hydrated particle size is 3-5 nm.

[0057] Example 5: Evaluation of ultra-small active nanofluid oil film stripping in low permeability reservoir flooding

[0058] Ultrapure water, 0.1wt% sodium petroleum sulfonate, 0.1wt% AES, 0.1wt% sodium dodecylbenzene sulfonate, and 0.1wt% ultra-small active nanofluid were prepared respectively. The oil film stripping experimental phenomena at different times were recorded with a high-definition camera at 50°C, and the oil film stripping efficiency was calculated using image J. The oil film stripping results are shown in Table 1 and Figure 5 shown.

[0059] Table 1

[0060]

[0061] From Table 1 and Figure 5 It can be seen that the oil film stripping efficiency of ultra-small active nanofluids has a higher stripping rate than that of surfactants with the same concentration, and the final oil film stripping rate is more than 25% higher than that of surfactants with the same concentration, showing a higher potential for improving crude oil recovery.

[0062] Example 6: Interfacial activity of ultra-small active nanofluids

[0063] Ultra-small active nanofluids with concentrations of 0wt%, 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, and 0.5wt% were prepared. The interfacial tensions of simulated oil, n-hexane, and ultra-small active nanofluids with different concentrations were tested at 60°C. See Tables 3 and Figure 6 .

[0064] At 60°C, the interfacial elastic modulus of simulated oil and ultra-small active nanofluids of different concentrations (0, 0.01wt%, 0.1wt%, 0.5wt%) was tested. The results are as follows: Figure 7 shown.

[0065] Table 3

[0066] Concentration / wt% 0 0.01 0.05 0.1 0.2 0.5 1.0 Simulated oil interfacial tension / (mN / m) 34.38 27.63 19.74 13.596 10.54 9.73 9.213 n-Hexane interfacial tension / (mN / m) 40.30 30.43 21.03 14.14 12.02 10.35 9.66

[0067] From Table 3 and Figure 6 , Figure 7 It can be seen that ultra-small active nanofluids can reduce the oil-water interfacial tension, increase the viscoelastic modulus of the oil-water interface, and have good interfacial activity.

[0068] Example 7: Ultra-small size active nanofluid core flooding experiment

[0069] The spontaneous imbibition method in the literature was used to evaluate the oil drainage capacity.

[0070] The experimental steps are:

[0071] ① Weigh the dry mass of the low-permeability outcrop cores and measure their permeability and porosity by gas measurement;

[0072] ② Vacuum saturated formation to saturate simulated oil;

[0073] ③ The outcrop cores are weighed as wet masses;

[0074] ④ At 60℃, water was first injected for displacement, and after the water flooding was completed;

[0075] ⑤ Inject 0.1wt% of ultra-small active nanofluid for displacement. The displacement flow chart is as follows: Figure 8a As shown;

[0076] ⑥ Read the oil volume driven out at different times and calculate the recovery rate. Figure 8b .

[0077] The results show that the recovery rate of the core is 15.8% higher than that of water, showing a good oil displacement capacity and can significantly improve the recovery rate of low permeability reservoirs.

[0078] Example 8: Low-field NMR experiment of ultra-small active nanofluids

[0079] As in Example 7, the saturated core method was consistent, and 0.1 wt% of ultra-small size active nanofluid was prepared with heavy water. The changes in T2 spectra at different displacement times were tested by online low-field nuclear magnetic resonance. The experimental results are shown in Fig. 9 The experimental results show that ultra-small active nanofluids can effectively mobilize crude oil in small and medium pores, thereby effectively improving the recovery rate of low permeability reservoirs.

[0080] Example 9

[0081] A method for preparing ultra-small active nanofluids comprises the following steps:

[0082] (1) Preparation of ultra-small active nano-silicon dot solid powder;

[0083] (2) dissolving the ultra-small size active nano silicon dot solid powder in water to prepare an ultra-small size active nano silicon dot mother solution for later use;

[0084] (3) Add water to the ultra-small active nano-silicon dot mother solution under stirring conditions to dilute it to a concentration of 0.05 wt%.

[0085] Furthermore, in parts by mass, step (1) comprises:

[0086] (11) 0.3 parts of trisodium citrate was dissolved in 7 parts of ultrapure water, nitrogen was introduced for protection, and then 1.5 parts of 3-aminopropyltrimethoxysilane was added, and stirred at room temperature to obtain a mixed solution; the mixed solution was added to a high-pressure reactor, the temperature was raised to 100° C., and the reaction was carried out for 48 hours to obtain an ultra-small-sized nano-silicon dot solution;

[0087] (12) adding 8 parts of a 20 wt% glutaraldehyde aqueous solution and 2 parts of p-phenylenediamine to 35 parts of ultrapure water, stirring at room temperature for 5 hours, adding the ultra-small-sized nano-silicon dot solution obtained in step (11), and continuing to stir at room temperature for 5 hours to obtain a mixed solution;

[0088] (13) 4 parts of sodium p-aminobenzenesulfonate and 8 parts of glutaraldehyde were added to the mixture obtained in step (12), and the mixture was stirred at room temperature for 5 hours. After freeze-drying, an ultra-small active nano-silicon dot solid powder was obtained.

[0089] The ultra-small active nanofluid is used as an oil displacement agent for low permeability reservoirs.

[0090] Furthermore, the reservoir temperature of the low permeability oil reservoir is 60°C.

[0091] Example 10

[0092] A method for preparing ultra-small active nanofluids comprises the following steps:

[0093] (1) Preparation of ultra-small active nano-silicon dot solid powder;

[0094] (2) dissolving the ultra-small size active nano silicon dot solid powder in water to prepare an ultra-small size active nano silicon dot mother solution for later use;

[0095] (3) Add water to the ultra-small active nano-silicon dot mother solution under stirring conditions to dilute it to a concentration of 0.2 wt%.

[0096] Furthermore, in parts by mass, step (1) comprises:

[0097] (11) dissolving 0.5 parts of trisodium citrate in 9 parts of ultrapure water, introducing nitrogen gas for protection, and then adding 2.5 parts of 3-aminopropyltrimethoxysilane, stirring at room temperature to obtain a mixed solution; adding the mixed solution to a high-pressure reactor, heating to 240° C., and reacting for 48 hours to obtain an ultra-small-sized nano-silicon dot solution;

[0098] (12) adding 12 parts of a 30 wt% glutaraldehyde aqueous solution and 4 parts of p-phenylenediamine to 45 parts of ultrapure water, stirring at room temperature for 10 hours, adding the ultra-small-sized nano-silicon dot solution obtained in step (11), and continuing to stir at room temperature for 10 hours to obtain a mixed solution;

[0099] (13) 6 parts of sodium p-aminobenzenesulfonate and 12 parts of glutaraldehyde were added to the mixed solution obtained in step (12), and the mixture was stirred at room temperature for 10 hours. After freeze-drying, an ultra-small-sized active nano-silicon dot solid powder was obtained.

[0100] The ultra-small active nanofluid is used as an oil displacement agent for low permeability reservoirs.

[0101] Furthermore, the reservoir temperature of the low permeability oil reservoir is 120°C.

[0102] Embodiment 11

[0103] A method for preparing ultra-small active nanofluids comprises the following steps:

[0104] (1) Preparation of ultra-small active nano-silicon dot solid powder;

[0105] (2) dissolving the ultra-small size active nano silicon dot solid powder in water to prepare an ultra-small size active nano silicon dot mother solution for later use;

[0106] (3) Add water to the ultra-small active nano-silicon dot mother solution under stirring conditions to dilute it to a concentration of 0.1 wt%.

[0107] Furthermore, in parts by mass, step (1) comprises:

[0108] (11) 0.4 parts of trisodium citrate was dissolved in 8 parts of ultrapure water, nitrogen was introduced for protection, and then 2 parts of 3-aminopropyltrimethoxysilane were added, and stirred at room temperature to obtain a mixed solution; the mixed solution was added to a high-pressure reactor, the temperature was raised to 160° C., and the reaction was carried out for 24 hours to obtain an ultra-small-sized nano-silicon dot solution;

[0109] (12) adding 10 parts of a 25 wt% glutaraldehyde aqueous solution and 3 parts of p-phenylenediamine to 40 parts of ultrapure water, stirring at room temperature for 8 hours, adding the ultra-small-sized nano-silicon dot solution obtained in step (11), and continuing to stir at room temperature for 8 hours to obtain a mixed solution;

[0110] (13) 5 parts of sodium p-aminobenzenesulfonate and 10 parts of glutaraldehyde were added to the mixed solution obtained in step (12), and the mixture was stirred at room temperature for 7 hours. After freeze-drying, an ultra-small-sized active nano-silicon dot solid powder was obtained.

[0111] The ultra-small active nanofluid is used as an oil displacement agent for low permeability reservoirs.

[0112] Furthermore, the reservoir temperature of the low permeability oil reservoir is 90°C.

[0113] The above describes the embodiments of the present invention in detail. However, the present invention is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A method for preparing ultra-small active nanofluids, characterized in that: The following steps are involved: (1) Preparation of ultra-small active nano-silicon dot solid powder; (2) dissolving the ultra-small size active nano silicon dot solid powder in water to prepare an ultra-small size active nano silicon dot mother solution for later use; (3) Add water to the ultra-small active nano-silicon dot mother solution under stirring conditions to dilute it to a concentration of 0.1 wt %, wherein: Step (1) comprises: (11) dissolving 0.3-0.5 parts of trisodium citrate in 7-9 parts of ultrapure water, introducing nitrogen gas for protection, and then adding 1.5-2.5 parts of 3-aminopropyltrimethoxysilane, stirring at room temperature to obtain a mixed solution; adding the mixed solution into a high-pressure reactor, heating to 100-240° C., and reacting for 1.5-48 hours to obtain an ultra-small-sized nano-silicon dot solution; (12) adding 8 to 12 parts of a 20 to 30 wt% glutaraldehyde aqueous solution and 2 to 4 parts of p-phenylenediamine to 35 to 45 parts of ultrapure water, stirring at room temperature for 5 to 10 hours, adding the ultra-small-sized nano-silicon dot solution obtained in step (11), and continuing to stir at room temperature for 5 to 10 hours to obtain a mixed solution; (13) adding 4 to 6 parts of sodium p-aminobenzenesulfonate and 8 to 12 parts of glutaraldehyde to the mixed solution obtained in step (12), continuing to stir at room temperature for 5 to 10 hours, and freeze-drying to obtain an ultra-small size active nano-silicon dot solid powder; The ultra-small size active nanofluid is composed of the following substances: Ultra-small active nano-silicon dots, with a content of 0.1wt%; The water content is 99.9wt%, of which: The water contains K + 、Na + Mg 2+ , Ca 2+ and Cl - of water, of which K + 、Na + The total concentration is 1000~30000mg / L, Ca 2+ and Mg 2+ The total concentration is 100-2000 mg / L, and the total mineralization is 2000-60000 mg / L; The particle size of the ultra-small active nano silicon dots is 3-5 nm.

2. Application of the ultra-small active nanofluid prepared by the preparation method of claim 1 as an oil displacement agent for low permeability reservoirs.

3. The use according to claim 2, characterized in that The reservoir temperature of the low permeability oil reservoir is 60-120°C.

Citation Information

Cited By

  • Biodegradable nanofluid heat exchange agent

    CN121518116A